2010
DOI: 10.1080/14616734.2010.501983
|View full text |Cite
|
Sign up to set email alerts
|

The Mothers and Toddlers Program, an attachment-based parenting intervention for substance using women: Post-treatment results from a randomized clinical pilot

Abstract: This is a report of post-treatment findings from a completed randomized pilot study testing the preliminary efficacy of The Mothers and Toddlers Program (MTP), a 12 week attachment-based individual parenting therapy for mothers enrolled in substance abuse treatment and caring for children ages birth to 36 months. Forty-seven mothers were randomized to MTP versus the Parent Education Program (PE) -a comparison intervention providing individual case management and child guidance brochures. At post-treatment, MTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
254
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(267 citation statements)
references
References 56 publications
12
254
1
Order By: Relevance
“…al., 2010; Suchman et al, 2010). We retained the authors' labels of a comparison as standard of care or active intervention, although the differences between the two were not always obvious.…”
Section: Data Extraction and Preparationmentioning
confidence: 99%
“…al., 2010; Suchman et al, 2010). We retained the authors' labels of a comparison as standard of care or active intervention, although the differences between the two were not always obvious.…”
Section: Data Extraction and Preparationmentioning
confidence: 99%
“…MTP is an attachment-based parenting intervention designed to enhance parent-child relationships by improving maternal refl ective functioning and the quality of the mother's mental representations of the child (e.g., being fl exible and balanced as opposed to infl exible and distorted). Researchers at Yale University School of Medicine recently reported the results of a pilot study involving 47 mothers who were enrolled in substance abuse treatment and caring for a child aged birth to 3 years (Suchman et al 2010(Suchman et al , 2011. Mothers were randomly assigned to participate in 12 weekly sessions of MTP or a comparison parenting education intervention.…”
Section: Programs Subject To Recent Randomized Trialsmentioning
confidence: 99%
“…In a pilot study examining MTP in a small sample of 14 substance-involved mothers of toddlers who ranged in age from 12 to 36 mo, preliminary pre-postcomparisons indicated that MTP was effective in increasing mothers' reflective functioning, sensitivity to child cues, and responses to child distress (12). These mechanisms of change also improved mothers' depressive symptoms, abstinence from drugs, and responsive caregiving to their children's cues as well as their children's clarity of cues immediately posttreatment and at 6-wk follow-up in a sample of 47 substanceinvolved mothers of young children (i.e., ranging in age from birth to 36 mo) who were randomized to MTP or a parent education program (13,70).…”
Section: Attachment-based Parenting Interventionsmentioning
confidence: 99%
“…This program can serve as an adjunct to individual substance abuse treatment and was developed to improve caregiving behavior by intervening at the level of maternal reflective functioning and representation quality (69). Within regard to reflective functioning, this intervention addresses mothers' ability to identify and downregulate their own distressing emotions as well as their ability to recognize and empathize with their children's emotions and needs (13,70). In a pilot study examining MTP in a small sample of 14 substance-involved mothers of toddlers who ranged in age from 12 to 36 mo, preliminary pre-postcomparisons indicated that MTP was effective in increasing mothers' reflective functioning, sensitivity to child cues, and responses to child distress (12).…”
Section: Attachment-based Parenting Interventionsmentioning
confidence: 99%